Reduced expressions of apoptosis-related proteins TRAIL, Bcl-2, and TNFR1 in NK cells of juvenile-onset systemic lupus erythematosus patients: relations with disease activity, nephritis, and neuropsychiatric involvement - Liphaus, Bernadete L.; Silva, Simone C.; Palmeira, Patrícia; Silva, Clovis A.; Goldenstein-Schainberg, Claudia; Carneiro-Sampaio, Magda (Frontiers in Immunology, 2024)
Background: Lupus pathogenesis is mainly ascribed to increased production and/or impaired clearance of dead cell debris. Although self-reactive T and B lymphocytes are critically linked to lupus development, neutrophils, monocytes, and natural killer (NK) cells have also been implicated. This study assessed apoptosis-related protein expressions in NK cells of juvenile-onset systemic lupus erythematosus (jSLE) patients, and related to disease activity parameters, nephritis, and neuropsychiatric involvement. Methods: Thirty-six jSLE patients, 13 juvenile dermatomyositis (JDM) inflammatory controls, and 9 healthy controls had Fas, FasL, TRAIL, TNFR1, Bcl-2, Bax, Bim and caspase-3 expressions in NK cells (CD3-CD16+CD56+) simultaneously determined by flow cytometry. Disease activity parameters included SLEDAI-2K score, ESR, CRP, anti-dsDNA, C3, and C4.Results: jSLE patients had a profile of significantly reduced expression of TRAIL, Bcl-2, and TNFR1 proteins in NK cells when compared to healthy controls. Similar profile was observed in jSLE patients with active disease, positive anti-dsDNA, nephritis, and without neuropsychiatric involvement. jSLE patients with positive anti-dsDNA also had reduced expression of Bax in NK cells when compared healthy controls and to those with negative anti-dsDNA. Yet, jSLE patients with negative anti-dsDNA had reduced MFI of Bim in NK cells compared to healthy controls. jSLE patients with nephritis also had reduced MFI of Fas in NK cells when compared to those without nephritis. In addition, in jSLE patients, the proportion of FasL-expressing NK cells directly correlated with the SLEDAI-2K score (rs =0.6, p=0.002) and inversely correlated with the C3 levels (rs= -0.5, p=0.007). Moreover, jSLE patients had increased NK cells percentage, and caspase-3 protein expression in NK cells when compared to JDM controls.This study extends to NK cells an altered profile of TRAIL, Bcl-2, TNFR1, Fas, FasL, Bax, Bim, and caspase-3 proteins in jSLE patients, particularly in those with active disease, positive anti-dsDNA, nephritis, and without neuropsychiatric involvement. This change in apoptosis-related protein expressions may contribute to the defective functions of NK cells, and consequently to lupus development. The full clarification of the role of NK cells in jSLE pathogenesis may pave the way for new therapies like those of NK cell-based.